Logic-based program synthesis and transformation : 24th International Symposium, LOPSTR 2014, Canterbury, UK, September 9-11, 2014. Revised selected papers /: 24th International Symposium, LOPSTR 2014, Canterbury, UK, September 9-11, 2014. Revised selected papers. (2015) - Unknown
No abstract available